Santripreneur Based on Islamic Business Ethics: Entrepreneurial Self-Reliance Practices at Ar-Ridho Sentul Modern Islamic Boarding School - Sumpena, Mochamad (DAYAH: Journal of Islamic Education, 2026)
This study explores how entrepreneurial self-reliance among students is developed through the integration of Islamic business ethics at the Ar-Ridho Sentul Modern Islamic Boarding School in Bogor, Indonesia. Employing a qualitative case study approach, data were collected through in-depth interviews with key stakeholders and documentation of entrepreneurial activities, including canteens, cooperatives, and online businesses managed by students. The data were analyzed descriptively to identify patterns related to entrepreneurial self-reliance, ethical practice, and institutional support. The findings indicate that Islamic business ethics are positioned as a moral foundation for students’ entrepreneurial activities, supported by leadership commitment, ethical guidance, and practical involvement in business units. The study also notes limitations related to experience and human resources and discusses opportunities and potential threats in relation to the application of ethical principles such as justice, transparency, and social responsibility. The study concludes that integrating Islamic business ethics into entrepreneurial practices in this pesantren is closely associated with the development of students’ entrepreneurial self-reliance and value-based entrepreneurship aligned with Islamic teachings. Abstrak Penelitian ini mengeksplorasi bagaimana kemandirian kewirausahaan siswa dikembangkan melalui integrasi etika bisnis Islam di Pesantren Modern Ar-Ridho Sentul, Bogor, Indonesia. Dengan pendekatan studi kasus kualitatif, data dikumpulkan melalui wawancara mendalam dengan pemangku kepentingan utama serta dokumentasi kegiatan kewirausahaan, termasuk kantin, koperasi, dan jual-beli online yang dikelola oleh siswa. Data dianalisis secara deskriptif untuk mengidentifikasi pola terkait kemandirian kewirausahaan, praktik etis, dan dukungan kelembagaan. Temuan menunjukkan bahwa etika bisnis Islam diposisikan sebagai landasan moral bagi aktivitas kewirausahaan siswa, dengan dukungan komitmen kepemimpinan, bimbingan etis, dan keterlibatan langsung dalam unit usaha. Studi ini juga mencatat keterbatasan pengalaman dan sumber daya manusia serta membahas peluang dan potensi ancaman dalam kaitannya dengan penerapan prinsip keadilan, transparansi, dan tanggung jawab sosial. Kesimpulannya, integrasi etika bisnis Islam dalam praktik kewirausahaan di pesantren ini berkaitan dengan pengembangan kemandirian kewirausahaan siswa dan kewirausahaan berbasis nilai yang selaras dengan ajaran Islam.